Barrier-free duct muffler for low-frequency sound absorption - Gao, Cong; Hu, Chuandeng; Mei, Jun; Hou, Bo; Zhang, Xianli; Du, Zhanhang; Wen, Weijia (Frontiers in Materials, 2022)
We demonstrate a duct muffler design operating at low frequency range (<2000Hz). The device contains a pair of coupled annular Helmholtz Resonators (HRs) and porous material stuffing. The HRs are installed as side branches of a circular ventilation tube to avoid affecting the ventilation. Porous material is employed to form asymmetric intrinsic loss in the HR pair and enables device to conduct perfect sound absorption. Analytical model based on temporal coupled-mode theory is derived and numerical simulation technique for structure design are introduced and verified. Experimental study demonstrates the effectiveness of the design methodology and illustrates that the device can achieve near perfect sound absorption in the desired frequency range. A symmetry configuration of HRs also experimentally proved to be able to conduct sound absorption for sound incident from both sides of the duct. This work provides a solid foundation for the application of the designed muffler and an analytical explanation of the corresponding sound absorption mechanisms.